2019
DOI: 10.2147/ijn.s193576
|View full text |Cite
|
Sign up to set email alerts
|

<p>Gadolinium-doped bioglass scaffolds promote osteogenic differentiation of hBMSC via the Akt/GSK3&beta; pathway and facilitate bone repair in vivo</p>

Abstract: BackgroundBiomaterial-induced osteogenesis is mainly related to hierarchically porous structures and bioactive components. Rare earth elements are well known to promote osteogenesis and stimulate bone repair; however, the underlying biological effects of gadolinium (Gd) element on bone regeneration are not yet known.MethodsIn this study, we successfully fabricated gadolinium-doped bioglass (Gd-BG) scaffolds by combining hollow mesoporous Gd-BG microspheres with chitosan and evaluated in vitro effects and under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…Moreover, the invivo results show that bone regeneration ability was higher for Gd doped BG than undoped BG. 39 For this reason, the trivalent lanthanide ion Gd 3+ was added along with these minerals on the HAP matrix.…”
Section: Dovepressmentioning
confidence: 99%
“…Moreover, the invivo results show that bone regeneration ability was higher for Gd doped BG than undoped BG. 39 For this reason, the trivalent lanthanide ion Gd 3+ was added along with these minerals on the HAP matrix.…”
Section: Dovepressmentioning
confidence: 99%
“…Rare-earth ions, including Ho 3+ , have ionic radii similar to Ca 2+ , acting either as agonist or antagonist of Ca 2+ sites in biochemical pathways, and can stimulate pre-osteoblastic cell proliferation [ 71 ]. Recently, Zhu et al [ 72 ] showed that Gd 3+ ions leached from bioactive glasses could stimulate protein expression related to the Wnt signaling pathway, which is related to osteogenic differentiation of human bone marrow-derived mesenchymal stem cell. In this mechanism, Gd 3+ ions would be related to increased expression of protein kinase B (Akt) and glycogen synthase kinase β (GSK3β), which together form the Akt/GSK3β pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to melt-derived compositions, where sol-gel derived compositions offer considerable freedom in process parameters, mesoporous glasses provide porosities for drug loading and controlled local delivery [67]. Coupled with a wide range of fabrication methods and processes, where freeze-drying is rapidly evolving into the method of choice owing to its simplicity and the geometrical flexibility [27,28,33,38,40,45,72]. Certain strategies appear more promising: For example, scaffolds seeded with MSCs that secrete B2BMP7, allowing for cells, the implanted scaffold, and secreted growth factors functioning synergistically in tissue regeneration [70].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, freeze-dried scaffolds of sol-gel derived, gadolinium-doped bioactive glass microspheres and chitosan have also been demonstrated to promote osteogenesis in calvarial defects in Sprague-Dawley rats. At 8 weeks post-implantation, significant increases in both new bone volume and bone mineral density are observed compared to equivalent scaffolds containing gadolinium-free bioactive glass [27].…”
Section: Collagen Gelatin Cellulose Chitosan and Other Biopolymersmentioning
confidence: 99%